Emerging roles of mechanosensitive ion channels in ventilator induced lung injury: a systematic review - Liu, Gang; Dong, Bin-bin; Devanarayana, Shalika; Chen, Rong-Chang; Liu, Qi (Frontiers in Immunology, 2024)
BackgroundThe pathogenetic mechanisms of ventilator-induced lung injury (VILI) still need to be elucidated. The mechanical forces during mechanical ventilation are continually sensed and transmitted by mechanosensitive ion channels (MSICs) in pulmonary endothelial, epithelial, and immune cells. In recent years, MSICs have been shown to be involved in VILI.MethodsA systematic search across PubMed, the Cochrane Library, Web of Science, and ScienceDirect was performed from inception to March 2024, and the review was conducted in accordance with PRISMA guidelines. The potential eligible studies were evaluated by two authors independently. Study characteristics, quality assessment, and potential mechanisms were analyzed.ResultsWe included 23 eligible studies, most of which were performed with murine animals in vivo. At the in vitro level, 52% and 48% of the experiments were conducted with human or animal cells, respectively. No clinical studies were found. The most reported MSICs include Piezo channels, transient receptor potential channels, potassium channels, and stretch-activated sodium channels. Piezo1 has been the most concerned channel in the recent five years. This study found that signal pathways, such as RhoA/ROCK1, could be enhanced by cyclic stretch-activated MSICs, which contribute to VILI through dysregulated inflammation and immune responses mediated by ion transport. The review indicates the emerging role of MSICs in the pathogenesis of VILI, especially as a signal-transmitting link between mechanical stretch and pathogenesis such as inflammation, disruption of cell junctions, and edema formation.ConclusionsMechanical stretch stimulates MSICs to increase transcellular ion exchange and subsequently generates VILI through inflammation and other pathogeneses mediated by MSICs signal-transmitting pathways. These findings make it possible to identify potential therapeutic targets for the prevention of lung injury through further exploration and more studies.Systematic review registrationhttps://inplasy.com/inplasy-2024-10-0115/, identifier INPLASY2024100115.